Smell and 3D Haptic Representation: A Common Pathway to Understand Brain Dynamics in a Cross-Modal Task. A Pilot OERP and fNIRS Study - Invitto, Sara; Montinaro, Roberta; Ciccarese, Vincenzo; Venturella, Irene; Fronda, Giulia; Balconi, Michela (Frontiers in Behavioral Neuroscience, 2019)
Cross-modal perception allows olfactory information to integrate with other sensory modalities. Olfactory representations are processed by multisensory cortical pathways, where the aspects related the haptic sensations are integrated. This complex reality allows the development of an integrated perception, where olfactory aspects compete with haptic and/or trigeminal activations. It is assumed that this integration involves both perceptive electrophysiological and metabolic/haemodynamic aspects, but there are no studies evaluating these activations in parallel. The aim of this study was to investigate brain dynamics during a cross-modal olfactory and haptic attention task, preceded by an exploratory session. The assessment of cross-modal dynamics was conducted through simultaneous electroencephalography (EEG) and functional Near-Infrared Spectroscopy (fNIRS) recording, evaluating both electrophysiological and haemodynamic activities. The study consisted of two experimental sessions and was conducted with a sample of ten healthy subjects (mean age 25± 5.2 years). In Session 1, the subjects were trained to manipulate 3-D haptic models (HC) and to smell different scents (SC). In Session 2, the subjects were tested during an attentive olfactory task, in order to investigate Olfactory Event Related Potentials (OERP) (N1 and Late Positive Component (LPC)) and EEG rhythms associated with fNIRS components (oxy-Hb and deoxy-Hb). The main results of this study highlighted, in Task 1, a higher fNIRS oxy-Hb response during SC, and a positive correlation with the delta rhythm in the central and parietal EEG region of interest. In Session 2, the N1 OERP highlighted a greater amplitude in SC. A negative correlation was found in HC for the deoxy-Hb parietal with frontal and central N1 and for the oxy-Hb frontal with N1 in the frontal, central and parietal ROIs. A negative correlation was found in parietal LPC amplitude with central deoxy-Hb. The data suggest that cross-modal valence modifies the attentional olfactory response and that the dorsal cortical/metabolic pathways are involved in these responses. This can be considered as an important starting point for understanding integrated cognition, as the subject could perceive in an ecological context.